Salmonella typhimurium and Lipopolysaccharide Stimulate Extracellularly Regulated Kinase Activation in Macrophages by a Mechanism Involving Phosphatidylinositol 3-Kinase and Phospholipase D as Novel Intermediates - Procyk, Katarzyna J. (American Society for Microbiology, 1999)
Activation of the extracellularly regulated kinase (ERK) pathway is part of the early biochemical events that follow lipopolysaccharide (LPS) treatment of macrophages or their infection by virulent and attenuated Salmonella strains. Phagocytosis as well as the secretion of invasion-associated proteins is dispensable for ERK activation by the pathogen. Furthermore, the pathways used by Salmonella and LPS to stimulate ERK are identical, suggesting that kinase activation might be solely mediated by LPS. Both stimuli activate ERK by a mechanism involving herbimycin-dependent tyrosine kinase(s) and phosphatidylinositol 3-kinase. Phospholipase D activation and stimulation of protein kinase C appear to be intermediates in this novel pathway of MEK/ERK activation.